2011
DOI: 10.1111/j.1540-8175.2010.01365.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Arterial Stiffness Indices in Different Vascular Territories and between Different Observers

Abstract: The reproducibility of ET derived AS parameters was good when AS was measured at the common carotid or femoral arteries. On the basis of our results brachial artery is probably not a reliable site for AS measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…DeMarzo (Demarzo, 2009) reported on the value of ICG in detecting subclinical vascular disease in women while we showed that impedance cardiography guided therapy was more effective than standard care in achieving hypertension control in subjects on more than one antihypertensive medication (Smith et al, 2006a). Pulse wave velocity and the augmentation index are now accepted methods for assessment of vascular stiffness (Hitsumoto, 2012; Rabkin et al, 2012; Salmi et al, 2012; Simova et al, 2011; Tomiyama and Yamashina, 2011; Yang et al, 2011; Zhang et al, 2013). The strength of our current research is based in having combined hemodynamic measures with non-invasive indexes of vascular compliance in concert with concomitant measures of hypertension-related biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…DeMarzo (Demarzo, 2009) reported on the value of ICG in detecting subclinical vascular disease in women while we showed that impedance cardiography guided therapy was more effective than standard care in achieving hypertension control in subjects on more than one antihypertensive medication (Smith et al, 2006a). Pulse wave velocity and the augmentation index are now accepted methods for assessment of vascular stiffness (Hitsumoto, 2012; Rabkin et al, 2012; Salmi et al, 2012; Simova et al, 2011; Tomiyama and Yamashina, 2011; Yang et al, 2011; Zhang et al, 2013). The strength of our current research is based in having combined hemodynamic measures with non-invasive indexes of vascular compliance in concert with concomitant measures of hypertension-related biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…(a) Aquisição da imagem para avaliação da rigidez arterial e (b) Onda de pulso aferida na artéria carótida.A pressão local na artéria carótida é tida como uma boa estimativa da pressão central, que é a mesma da aorta ascendente. Foram fornecidos, então, os dados que foram utilizados para a medida da rigidez arterial, aqui representada como velocidade de onda de pulso (VOP), a qual era expressa na tela do equipamento 123. …”
unclassified